Job stress and employee retention in textile crisis: the mediating role of organizational commitment - Al Ghozy, Abdul Fatah; Rohimat, Asep Maulana (Jurnal Mantik, 2025)
This study aims to analyze the effect of job stress on employee intention to remain and the mediating role of organizational commitment in the textile industry in Karanganyar Regency. The crisis in the textile sector, due to decreased export demand, import competition, and government policies, has an impact on organizational performance. This study uses an explanatory research design with a quantitative approach. The sample of 150 respondents was permanent employees of textile companies affected by the textile crisis in January-October 2024, selected using purposive sampling technique. Data were analyzed using SEM-PLS. The results show that job stress negatively affects intention to remain and commitment, which means that low job stress increases employees' intention to stay and organizational commitment. Organizational commitment mediates the relationship between job stress and intention to remain, which means that the desire to stay in the company is high because it is driven by the high organizational commitment of employees